Predictors of overweight and obesity and its consequences among Senoi Orang Asli (indigenous people) women in Perak, Malaysia - Law, Leh Shii; Sulaiman, Norhasmah; Gan, Wan Ying; Adznam, Siti Nur'asyura; Mohd Taib, Mohd Nasir (MDPI, 2020)
In spite of the high prevalence of overweight and obesity among the Orang Asli (OA) of Malaysia being an increasing concern due to the associated adverse health implications, information regarding this issue is scarce. This cross-sectional study is aimed to investigate the predictors of overweight and obesity and its association with blood pressure and quality of life among Senoi OA women. A total of 19 villages at Batang Padang, Perak, were selected out of a total of 56 villages using a simple random sampling, in which 355 Senoi OA women were participated in the study. Face-to-face interviews were conducted to obtain information on sociodemographic characteristics, dietary intake, physical activity, and quality of life. Weight, height and blood pressure were also measured. The prevalence of overweight and obesity were 32.4% and 26.2%, respectively. In terms of multiple linear regression, monthly household income, total energy intake, and metabolic equivalents (METs) for domestic activities were found to have significantly contributed to body mass index (BMI). Furthermore, BMI contributed significantly towards levels of blood pressure and quality of life after controlling for monthly household income, total energy intake, and METs for domestic activities. In conclusion, there should be urgent attention to poverty and overweight/obesity among the OA women. The findings would aid in alerting policy makers and health professionals as underweight is no longer a sole nutritional problem among OA but it appears to be coexisting with overweight and obesity. Strategies for improving their socioeconomic status, promoting a balanced and moderate diet, and encouraging involvement of OA women in physical activities should be implemented to prevent overweight and obesity.